2012
DOI: 10.1029/2011ja017044
|View full text |Cite
|
Sign up to set email alerts
|

Metallic species, oxygen and silicon in the lunar exosphere: Upper limits and prospects for LADEE measurements

Abstract: [1] The only species that have been so far detected in the lunar exosphere are Na, K, Ar, and He. However, models for the production and loss of species derived from the lunar regolith through micrometeoroid impact vaporization, sputtering, and photon-stimulated desorption, predict that a host of other species should exist in the lunar exosphere. Assuming that loss processes are limited to ballistic escape, photoionization, and recycling to the surface, we have computed column abundances and compared them to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 67 publications
1
84
1
2
Order By: Relevance
“…Other sources for argon include surface sputtering, but Wurz et al (2007) demonstrated that it is a negligible process, at least for argon (Sarantos et al (2012) showed that it is not so for refractories and metals). While an important source for the lunar helium exosphere, the solar wind delivers very little 40 Ar compared to 36 Ar, as demonstrated by Yaniv and Heymann (1972).…”
Section: Lifetime (S)mentioning
confidence: 97%
“…Other sources for argon include surface sputtering, but Wurz et al (2007) demonstrated that it is a negligible process, at least for argon (Sarantos et al (2012) showed that it is not so for refractories and metals). While an important source for the lunar helium exosphere, the solar wind delivers very little 40 Ar compared to 36 Ar, as demonstrated by Yaniv and Heymann (1972).…”
Section: Lifetime (S)mentioning
confidence: 97%
“…modeled the soft X-ray intensities produced by charge exchange at the Moon and predicted them to be about 10 keV cm −2 s −1 sr −1 , comparable to the diffuse cosmic X-ray background (Lumb et al 2002). presented observations of limb brightening in the ROSAT lunar data consistent with the expected signal from solar wind charge exchange with the lunar exosphere and compared these observations to the predictions of hybrid simulations for solar wind ion access to regions behind the terminator of the Moon Farrell et al 2008;Fatemi et al 2012) and models of the lunar exosphere (Sarantos et al 2012;Tenishev et al 2013). Of particular note is that the soft X-rays produced by charge exchange can provide diagnostics on the entire neutral exospheric density including all species, whereas other techniques are spectroscopic in nature and observe particular lines, for example Na (Potter et al 2000).…”
Section: The Moonmentioning
confidence: 97%
“…A number of observational studies have constrained neutral source densities [Feldman and Morrison, 1991;Flynn and Stern, 1996;Stern et al, 1999;Cook et al, 2013]; however, these studies placed only upper limits on many species. We therefore compare our inferred production rates to modeled distributions [Wurz et al, 2007;Sarantos et al, 2012aSarantos et al, , 2012bPoppe et al, 2016].…”
Section: Inferred Ion Production Rates and Exospheric Source Structurementioning
confidence: 99%